The Urgency Of Fulfilling The Rights To Health Of Elderly Prisoners In Prisons - Mitro Subroto; Ronaldo Efraim Lubis (YUSTISIA MERDEKA : Jurnal Ilmiah Hukum, 2025)
Abstract Introduction to the Problem: Elderly prisoners face significant challenges in accessing adequate healthcare within correctional institutions. Limited facilities, lack of trained personnel, and ineffective implementation of health policies contribute to disparities in healthcare services, affecting their physical and mental well-being. Purpose/Study Objectives: This study aims to explore the urgency of fulfilling the health rights of elderly prisoners, identifying barriers to healthcare access and proposing systemic improvements to enhance their well-being. Design/Methodology/Approach: The research employs a qualitative approach, collecting data through in-depth interviews with 15 elderly prisoners and 10 prison officers, as well as conducting observations on prison health conditions. Findings: The study highlights several key issues, including inadequate healthcare facilities, insufficient medical resources, and a lack of proper training for prison officers. Additionally, existing health policies in prisons are not effectively implemented, leading to disparities in healthcare access. The research emphasizes the need for systemic improvements, such as officer training and policy reinforcement, to ensure better healthcare for elderly prisoners. Paper Type: This is an empirical research study based on qualitative analysis.